Efficiency enhancement of Raman spectroscopy at long working distance by parabolic reflector - Tian, Yao (2017)
Raman spectroscopy is well suited for readily revealing information about bio-samples. As such, this technique has been applied to a wide range of areas, particularly in bio-medical diagnostics. Raman scattering in bio-samples typically has a low signal level due to the nature of inelastic scattering of photons. To achieve a high signal level, usually a high numerical aperture objective is employed. One drawback with these objectives is that their working distance is very short. However, in many cases of clinical diagnostics, a long working distance is preferable. We propose a practical solution to this problem by enhancing the Raman signal using a parabolic reflector. The high signal level is achieved through the large light collection solid angle of the parabolic reflector while the long working distance is ensured by the novel design of our microscope. The enhancement capability of the microscope was demonstrated on four types of samples. Among these samples, we find that this microscope design is most suitable for turbid samples.